Real-world treatment patterns, discontinuation and clinical outcomes in patients with B-cell lymphoproliferative diseases treated with BTK inhibitors in China - Yan, Yuting; Lv, Rui; Wang, Tingyu; Yu, Ying; Huang, Yanshan; Xiong, Wenjie; Li, Yuxi; Sui, Weiwei; Wang, Qi; Huang, Wenyang; An, Gang; Zou, Dehui; et al. (Frontiers in Immunology, 2023)
Bruton tyrosine kinase inhibitor (BTKi) has demonstrated substantial efficacy in treating B-cell lymphoproliferative diseases (BLPD). Nonetheless, the significant discontinuation rates due to toxicity or financial reasons cannot be overlooked. In China, empirical evidence on the usage of BTKi remains scarce. To address this, a retrospective cohort study was conducted focused on 673 Chinese patients with BLPD who underwent at least one month of BTKi therapy. Median age at BTKi initiation was 60 years. The median duration on BTKi treatment of the whole cohort was 36.4 months. The median post-BTK survival was not reach. BTKi-based treatment was permanently discontinued in 288 (43.8%) patients during follow-up, mostly attributed to progressive disease. Within the first 6 months of BTKi treatment, 76 patients (26.3%) had early treatment discontinuation. Patients with early discontinuation had extreme worse outcome with a median post-discontinuation survival of only 6.9 months. On multivariate analysis, withdrawal BTKi by toxicity and withdrawal BTKi within 6 months retained to be independent predictors of post-BTK survival, after taking account of the response depth, lines of therapy and baseline cytogenetics including 17p deletion. The decision between BTKi monotherapy and combination therapy, along with the preference for first or second-generation BTKi, exerted no significant impact on survival. These observations contribute valuable real-world insights into the utilization of BTKi in China. We concluded that BTKi is an effective and well-tolerated treatment for long-term use in Chinese patient population. However, it is imperative to stress that a proportion of patients discontinue BTKi early, leading to suboptimal outcomes. This study underscores the importance of adherence to BTKi therapy for improved clinical outcomes in real-world patients.